2016
DOI: 10.1002/2015gl067366
|View full text |Cite
|
Sign up to set email alerts
|

Weakening of Jupiter's main auroral emission during January 2014

Abstract: In January 2014 Jupiter's FUV main auroral oval decreased its emitted power by 70% and shifted equatorward by ∼1°. Intense, low‐latitude features were also detected. The decrease in emitted power is attributed to a decrease in auroral current density rather than electron energy. This could be caused by a decrease in the source electron density, an order of magnitude increase in the source electron thermal energy, or a combination of these. Both can be explained either by expansion of the magnetosphere or by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 55 publications
4
39
1
Order By: Relevance
“…The image taken on DOY140 is shown as a representative for the quiet period (Figure b). Between 02:17:42 and 03:02:12 (DOY142.10–142.13) on DOY142 (Figures c–e), a dawn storm, which is suggestive of dawnside tail reconnection and planetward return flow [ Cowley et al , ; Clarke et al , ], was evident at System III longitude of 180°–260° less than in the main oval (Figures c–e) as observed during the 2014 HST campaign [ Kimura et al , ; Badman et al , ; Gray et al , ]. This exposure time corresponds to the onset timing of the transient aurora in the Hisaki data.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The image taken on DOY140 is shown as a representative for the quiet period (Figure b). Between 02:17:42 and 03:02:12 (DOY142.10–142.13) on DOY142 (Figures c–e), a dawn storm, which is suggestive of dawnside tail reconnection and planetward return flow [ Cowley et al , ; Clarke et al , ], was evident at System III longitude of 180°–260° less than in the main oval (Figures c–e) as observed during the 2014 HST campaign [ Kimura et al , ; Badman et al , ; Gray et al , ]. This exposure time corresponds to the onset timing of the transient aurora in the Hisaki data.…”
Section: Resultsmentioning
confidence: 91%
“…The simultaneous imaging by the Hubble Space Telescope (HST) with Hisaki indicated that the three structures introduced above, the main oval, poleward emissions, and outer emission, were enhanced simultaneously around the transient aurora [ Kimura et al , ; Badman et al , ; Gray et al , ]. However, the temporal and spatial evolutions of the transient aurora and energetic events were not resolved by these previous observations because of the lack of continuous monitoring that spans the typical duration of the transient aurora.…”
Section: Introductionmentioning
confidence: 99%
“…The dataset of the previous Jupiter observation campaign from December 2013 to January 2014 includes short-term (not longer than one Jovian planetary rotation) aurora intensifications under quiet SW conditions Badman et al 2016). These shortduration events were regarded as internally driven compared with intensifications lasting for more than 2 days under high SW pressure conditions, which were defined as externally driven .…”
Section: Discussionmentioning
confidence: 99%
“…An example of the main oval dominated control of the total auroral power can be found in the HST observation in Badman et al [2016], in which decreasing trend in the total auroral power was mainly caused by dimming of the main oval, possibly due to an expansion of the magnetosphere under decreasing solar wind dynamic pressure. That is, the main oval is assumed to be the main contributor to the auroral power enhancement in response to the elevated solar wind dynamic pressure.…”
Section: Discussionmentioning
confidence: 99%